Is it necessary for children to receive professional fluoride in addition to regular fluoride toothpaste? Protocol for a systematic review - Jun Li; Fang Hua; Lintong Yu; Xueqian Yu; Yueyang Li; Guangtai Song (BMJ Open)
Introduction Regular toothbrushing with fluoride toothpaste is a fundamental intervention for caries prevention. Professional fluoride application (PFA) is widely considered a beneficial supplement to the routine use of fluoride toothpaste. However, some recent studies have failed to demonstrate the preventive effect of PFA. In addition, an increasing number of studies have highlighted the potential adverse effects of fluoride. However, little information exists on the effectiveness of additional PFA. The objective of this review is to systematically analyse the efficacy of PFA in addition to regular fluoride toothpaste among children under the age of 16.Method and analysis We will search the PubMed, Embase, Google Scholar and Cochrane Central Register of Controlled Trials databases for randomised controlled trials without language or publication date restrictions. Additional studies will be identified by manually searching the reference lists of the included studies and relevant reviews. At least two authors will carry out the selection of studies independently and in duplicate. The Cochrane Risk of Bias tool will be used to assess the risk of bias of the included studies. The random effects model will be used for meta-analyses. The data synthesis will be conducted using Review Manager software (RevMan V.5.3). The Grading of Recommendation, Assessment, Development and Evaluation will be used to assess the quality of supporting evidence for each major comparison.Ethics and dissemination There is no need for ethical approval. The results of this review will be disseminated through peer-reviewed publications and social networks.PROSPERO registration number CRD42020165270